Confrontations between history and school: The Puquina in the Andean south - Mario Zapata Delgado (2020)
Since the existence of culture, language, and western Puquina ethnicity has been a focal point of linguistic, anthropological and historical studies, which has tried to demonstrate the existence of the Puquina in this area that goes from the basin of the Chili (Arequipa) to Atacama in some authors and others to the Sama in Tacna, the truth is that a historiographic current has been created based on "the idol of the origins" which presumes about the action puquina in this region, the truth is That what existed were enclaves, puquinas like Aymaras and Quechuas besides coli and a form of atacameño in the zone, then it is sought to reformulate its intervention and protagonism in the zone. We also note that a reinvention of the puquina is taking place in terms of cultural heritage, from the local government academia and citizen practices.